CHILDREN'S BOOK CREATION WITH PAPERCRAFT VARIATIONS AS INTRODUCTION TO RARE ANIMALS IN INDONESIA - Nugraha, Salistya Adi (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2019)
The development of technology makes children's reading interest begin to decrease. One effort can be made to increase children's reading interest by creating books with variations of Papercraft. Illustrated images of books characterized by rare animals and by adding variations of papercraft to add special charm, so that children will be more interested in reading them. The media used in this study project includes office stationery, printers, computers, and software. Materials include paper, adhesive, and ink. The stages in the work process include the initial stages of finding ideas, setting goals and analyzing the target audience. Furthermore, production is carried out starting with sketching, dummy, template processing and binding. The last stage is the post-production stage, which is the stage of the work that the author made, consulted with the supervisor then exhibited. The work of this study project has produced a dummy of children's books with variations of papercraft as an introduction to rare animals in Indonesia. This papercraft book is expected to attract children to play and learn about rare animals in Indonesia and papercraft. This book is also expected to provide inspiration and motivation to other illustrators to create works in the form of books by choosing different and more creative and varied themes